PROPERTIES OF CO-SPECTRA OF JOINT SPECTRA OF STRUCTURES (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2005)
Two properties of co-spectrum of joint spectrum of finitely many abstract structures are presented: a minimal pair type theorem and an existence of a quasi-minimal degree for the joint spectrum.